2006
DOI: 10.1007/s00384-005-0072-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome following mucosal advancement flap for high perianal fistulas and fistulotomy for low perianal fistulas

Abstract: The success rate of both FT and MF techniques decreases with time. Recurrence appears to be caused by failure of treatment and by recurrent patient disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
69
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 28 publications
2
69
0
11
Order By: Relevance
“…Where reported38 46, the recurrence rate at more than 1 year was 30–50 per cent. Complications were reported in only one study40, with haemorrhage and flap retraction occurring in 7 per cent.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Where reported38 46, the recurrence rate at more than 1 year was 30–50 per cent. Complications were reported in only one study40, with haemorrhage and flap retraction occurring in 7 per cent.…”
Section: Resultsmentioning
confidence: 93%
“…Longer‐term (6 months or more after treatment) fistula recurrence occurred in five of 28 patients30 and three of nine patients46 at 12 months. One study29 found that 22 of 27 patients had a ‘satisfactory’ outcome, although the five patients in whom the outcome was unsuccessful developed significant incontinence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations